Bioprospecting and Molecular Identification of Amylase and Cellulase Producing Thermophilic Bacteria from Sediment of Nglimut Hot Springs, Kendal Regency - Budiharjo, Anto; Wulandari, Dyah; Shabrina, Jauhara; Mawarni, Risa Arum; Maulana, Anand Reyna; Nurhayati, Nurhayati; Wijanarka, Wijanarka; Hartajanie, Laksmi; Lindayani, Lindayani (Journal of Tropical Biodiversity and Biotechnology, 2024)
The utilisation of enzymes in the industry has brought numerous benefits and advantages to production processes. Enzymes serve as biocatalysts, efficiently catalyzing reactions and hydrolysis in biochemical processes. However, there are challenges in applying enzymes in the industry, particularly concerning enzyme stability. The obstacle encountered in the production processes involving industrial enzyme applications is the low stability of enzymes when used at high temperatures. Heat-sensitive enzymes undergo damage or denaturation. Thermophilic microorganisms are chosen because they hold the potential to produce thermophilic enzymes. The thermophilic enzymes exhibit better heat stability compared to other enzymes, making them an effective alternative for future industrial production processes. This study aims to isolate thermotolerant bacteria from Nglimut Hot Spring sediment, screen for cellulase- and amylase-producing isolates, and molecularly identify the best isolate using 16S rRNA barcode. The results show that 22 bacterial isolates were found in the sediment of a hot spring; TS-14 was the best isolate in producing amylase, with the highest average amylolytic index of 2.38, whereas TS-15 had the highest cellulolytic index of 2.11. Based on 16S rRNA identification, TS-14 showed an homological identity of 79% with Bacillus amyloliquefaciens, while TS-15 had a 100% homological identity with Bacillus licheniformis. These results were important as the first step of screening bacterial potential to produce thermophilic enzymes that could be applied in the downstream processing in future industrial and biotechnology companies.